Pendampingan Kegiatan Posbindu Penyakit Tidak Menular Pada Masyarakat Buta Aksara - Bratajaya, Cicilia Nony Ayuningsih; Kadang, Yulta; Rahayu, Previarsi; Padaaallah, Ananda Patuh (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The low awareness of the signs of hypertension among wider community is a concern. The symptoms of dizziness that are often considered something normal, therefore they are ignored. As a result, over a long period of time the hypertension as a Non-Communicable Disease (NCD) increasingly due to serious complication as well as heart disease, stroke, and kidney failure. This Community outreach aims to provide Hypertension health education. The methods were organizing community, partnerships, health promotion, and health empowerment. The approach were carried out primarily with health cadres and collaborating with Primary Health Centre, furthermore the activities could held with Posbindu activities simultaneously. The result show that people who illiterate were able to increase their knowledge from 43.75% to 75% regarding the meaning of hypertension, signs and symptoms, complication, and hypertension treatment. Taking everything into account, it is necessary to strengthen cadres as health ambassadors in the community due to prevent NCD.